THE STRUCTURE OF THE SPIRITUAL EXERCISES OF SAINT IGNATIUS OF LOYOLA IN THE LIGHT OF THE TEACHING OF SAINT THOMAS AQUINAS ON THE ELECTION - Boday, Eugene (Divus Thomas, 1989)
This study is divided into two distinct parts. The first part describes the teaching of St. Thomas Aquinas on election according to his Summa which lists the following elements: preparation of election with four elements (the knowledge of the end, the knowledge of the means, the counsel to determine the objective better means, the desire to establish the subjective better means), the election itself, the execution of election, and the fruition obtained by the execution of the election. The second part is an application of this teaching to the exercises of Saint Ignatius. In the Principle and Foundation one can clearly find the four elements: God as the end of man; creatures as means; the counsel indifference, an added element as precondition to choose the better means; subjective appropriation by desire of the better means. In the First Week Saint Ignatius presents the tragedy of wrong election and shows that the only way out of this tragedy is salvation through Christ. The second week repeats the four elements in the present economy of salvation: Christ as the end, His mysteries as means, the counsel to determine the better means in the Two Standards, subjective appropriation by desire in The Three Kinds of Humility. By these meditations the retreatant is prepared to make the election which is the climax of the retreat. The execution of the election is contemplated in the Third and Fourth Week. The Paschal mystery unites us with the suffering and glorified Lord. The fruition of the election is presented in the Contemplatio ad amorem. Thus it is shown that in the light of the teaching of Saint Thomas, the exercises of Saint Ignatius have a remarkable, unified structure which binds all parts of the Exercises together and clarifies the whole corpus of their content. Finally, the question is explored that why is it that this unified structure shows itself in the Exercises. Though it is not primary objective of this study, nevertheless some facts are discussed which point to the possibility that Saint Ignatius was influenced by the teaching of Saint Thomas in his later revisions of the text of the Spiritual Exercises.